The Combination of Attributes that Becomes Consumer Preferences towards Ready-to-Drink Swallow Birdnest Beverasge Product - Raymond Koespianto; Bambang Sugiyono Agus Purwono (Universitas Ciputra Surabaya, 2023)
A healthy body helps human everyday’s activities that drives for their success. With the increase of people’s awareness for health, the demand for healthy instant products has become an opportunity that covers what the market needs. Seeing all the opportunities, the researcher has an idea to launch his own business independently which is to create a ready-to-drink swallow’s nest beverage product called “Fei Ran.” This study aims to determine the market demands so that this the launch of this business can go smoothly. The ready-to-drink swallow bird nest beverage product will consist of four attributes which are taste, packaging, price, and brand, each consisting of two levels. This research is supported using conjoint analysis which will assisted with the help of a computer software, where respondents will provide an assesment and make decisions according to their preferences from a total of 16 different combination of attributes for ready-to-drink swallow’s nest beverage product. From a total of 100 respondents ages ≥ 30 years that belongs to middle to upper class, the overall results show that the majority of consumer most preferred ready-to-drink swallow’s nest beverage product is a product that has Original as its taste, use bottle shaped packaging, price at Rp. 70,000 – 85,000, and has a brand design that has a red logo concept.